2003
DOI: 10.1034/j.1600-0765.2003.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator NF κB ligand (RANKL) and osteoprotegerin (OPG) protein expression in periodontitis

Abstract: The change in the levels of these key regulators of osteoclast differentiation may play a major role in the bone loss seen in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
236
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(276 citation statements)
references
References 42 publications
17
236
1
11
Order By: Relevance
“…Characteristic features of this disease include soft tissue inflammation in response to gram-negative anaerobic bacteria that collect in the gingival pockets and associated alveolar bone loss [87]. In periodontitis gingival tissues, increased numbers of multinucleated TRAP positive osteoclasts have been detected along with high levels of RANKL and corresponding low levels of its inhibitor osteoprotegerin (OPG) [37].…”
Section: Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic features of this disease include soft tissue inflammation in response to gram-negative anaerobic bacteria that collect in the gingival pockets and associated alveolar bone loss [87]. In periodontitis gingival tissues, increased numbers of multinucleated TRAP positive osteoclasts have been detected along with high levels of RANKL and corresponding low levels of its inhibitor osteoprotegerin (OPG) [37].…”
Section: Periodontitismentioning
confidence: 99%
“…In bone loss diseases, including osteoporosis, RA, periodontitis and multiple myeloma, increased numbers of osteoclasts and high levels of Receptor Activator of Nuclear Factor Kappa B ligand (RANKL) have been reported [37][38][39][40][41][42]. Over the past decade, numerous studies have shown that RANKL, produced by cytokine-activated lymphocytes, fibroblasts and plasma cells, drives excessive osteoclastmediated bone resorption in RA, periodontitis and multiple myeloma, respectively [37,38,40,43].…”
Section: Osteoclasts Hdacs and Hdacimentioning
confidence: 99%
“…RANKL is expressed in synovial tissue from patients with rheumatoid arthritis (27)(28)(29) and has been found to be crucial for osteoclast formation and bone loss in experimentally induced arthritis in mice (30). RANKL is also expressed in gingival tissue from patients with periodontal disease (31,32), and increased RANKL/OPG is associated with bone loss in periodontitis (4,31).…”
mentioning
confidence: 99%
“…Increased RANKL/OPG ratio accompanies bone resorption involved in a variety of processes such as pathological osteolysis (Grimaud et al, 2003;Tay et al, 2004), periodontitis (Crotti et al, 2003), tooth eruption (Heinrich et al, 2005), and orthodontic tooth movement (Yamaguchi, 2009). The current data adds physiologic mandibular periosteal growth to that list.…”
Section: Discussionmentioning
confidence: 85%